Breeding Leucaena for low-mimosine: Field evaluation of selections - Bray, RA; Hutton, E.M.; Beattie, WM (1984)
A breeding program to select low-mimosine lines of leucaena has been in progress since 1970. Selections were evaluated in two field trials at Lansdown. Although the low-mimosine selections did indeed have lower mimosine than the control cultivars, their dry matter yield was also inferior (about two-thirds of cv. Cunningham). Some possible reasons for this are discussed.